Digitalization of teaching and learning in TVET: a bibliometric analysis - Norazreen Othman; Marlissa Omar; Mohamad Sattar Rasul (Intelektual Pustaka Media Utama, 2026)
The rapid integration of digitalization in technical and vocational education and training (TVET) has gathered significant attention from researchers worldwide. This research conducted a comprehensive bibliometric analysis to explore the current landscape of digitalization of teaching and learning in TVET. The aims were to identify research trends, the most cited articles, type of document by subject area, top 10 authors, research hotspot, co-authorship analysis, and citation of article’s density. Bibliometric analysis techniques were employed by examining publication data spanning from 2015 to 2023, extracted from the Scopus database, particularly focusing on network visualization and clustering methods using VOSviewer software. The analysis revealed a steady increase in research output over the past decade, indicative of growing interest in the field. The distribution of publications among authors was balanced, indicating a collaborative research landscape. Nonetheless, there were swings in publishing rates, indicating the dynamic character of research goals and trends. Moreover, subject area analysis demonstrated a multidisciplinary approach reflecting the multifaceted nature of digitalization in TVET. By leveraging bibliometric analysis techniques, this research contributes to a deeper understanding of research trends, guiding future research directions and to advance innovative and sustainable practices in digital teaching and learning within TVET, thus benefiting learners, educators, and stakeholders.